The Role of Islamic Extension Workers in the Spiritual Mental Development of Kalurahan Civil Service in Patuk District - Harun Suyanto; Nawari Ismail (Ridwan Institute, 2023)
The role of Islamic religious instructors is as a guide and role model, and has a function as an educator and consultant for the community in the field of religion and society. The important role of extension workers is to increase the knowledge of the community, especially pamong kalurahan, regarding religious teachings and their implementation in everyday life. The goal is the importance of spiritual mental development for pamong kalurahan in the Patuk sub-district. This research method is to use a qualitative descriptive approach, namely observation, interviews, and documentation. While the validity of the data through triangulation (sources and methods). The data analysis technique uses the Miles and Huberman models, namely data reduction, data presentation, and drawing conclusions. The results of the research on the role of Islamic religious instructors are to provide guidance in various forms including periodic routine recitation activities, Islamic studies, household studies, and tutoring in reading the Qur'an. Extension officers provide assistance by giving advice either directly or indirectly.